Pengaruh Spiritual Emotional Freedom Technique terhadap Self-Acceptance Warga Binaan di Lembaga Pemasyarakatan Perempuan - Anjar Novitriani; Fina Hidayati (Psympathic : Jurnal Ilmiah Psikologi, 2018)
Being a prisoner often raise psychological conflicts. Prisoners often experience mental problems caused by social isolation in the prison, and it may leads to inferiority, guilty, and self-rejection. This study aims to examine the effect of Spiritual Emotional Freedom Technique (SEFT) therapy on self-acceptance of prisoners (Lembaga Pemasyarakatan Perempuan Klas II A Malang). This study used pretest-posttest control group design with purposive sampling of 15 participants for experimental group and 16 participants for control group. The results show that there was an increase from pretest to posttest with significant value of .021 (p<.050). This finding indicates that there is an influence of Spiritual Emotional Freedom Technique (SEFT) therapy on self-acceptance of prisoners (Lembaga Pemasyarakatan Perempuan Klas II A Malang).